Tensores fundamentais da formulação dos problemas elásticos axissimétricos pelo método dos elementos de contorno - Stikan, Rafael Pacheco (2006)
This work presents the Boundary Element formulation to axysimmetric elastic problems. The Kelvin solution, which uses a unitary concentrated load in an infinite elastic domain to generate the fundamental solution, is taken into account. Initially, the three-dimensional problem expressed in cartesian coordinates is transformed to cylindrical ones. In a second step the mathematical expressions are integrated in the “ ” variable, changing into a two-dimensional model. In this mathematical strategy occur elliptic integrals and their derivatives, which are manipulated to achieve the fundamental stresses. Cumbersome singular integrals would need to be solved using traditional collocation of source points on the boundary. Here the positions of source points are external to physical domain, avoiding singularities.